A survey of teaching undergraduate neuroanatomy in the United Kingdom and Ireland. (2nd January 2022) - Edwards-Bailey, Andrew; Ktayen, Howra; Solomou, Georgios; Bligh, Emily; Boyle, Abbey; Gharooni, Aref-Ali; Lim, Guan Hui Tricia; Varma, Adithya; Standring, Susan; Santarius, Thomas; Fountain, Daniel
Abstract: Background: Medical students' perception of neuroanatomy as a challenging topic has implications for referrals and interaction with specialists in the clinical neurosciences. Given plans to introduce a standardised Medical Licensing Assessment by 2023, it is important to understand the current framework of neuroanatomy education. This study aims to describe how neuroanatomy is taught and assessed in the UK and Ireland. Methods: A structured questionnaire capturing data about the timing, methods, materials, assessment and content of the 2019/2020 neuroanatomy curriculum in the UK and Ireland medical schools. Results: We received 24/34 responses. Lectures (96%) were the most widely used teaching method, followed by prosection (80%), e-learning (75%), tutorials/seminars (67%), problem-based learning (50%), case-based learning (38%), and dissection (30%). The mean amount of core neuroanatomy teaching was 29.3 hours. The most common formats of assessing neuroanatomical knowledge were multiple-choice exams, spot tests, and objective structured clinical exams. Only 37.5% schools required demonstration of core clinical competency relating to neuroanatomy. Conclusions: Our survey demonstrates variability in how undergraduate neuroanatomy is taught and assessed across the UK and Ireland. There is a role for development and standardisation of national undergraduate neuroanatomy curricula in order to improve confidence and attainment.